Immune- and Nonimmune-Compartment-Specific Interferon Responses Are Critical Determinants of Herpes Simplex Virus-Induced Generalized Infections and Acute Liver Failure - Parker, Zachary M. (J Virol, 2016)
The interferon (IFN) response to viral pathogens is critical for host survival. In humans and mouse models, defects in IFN responses can result in lethal herpes simplex virus 1 (HSV-1) infections, usually from encephalitis. Although rare, HSV-1 can also cause fulminant hepatic failure, which is often fatal. Although herpes simplex encephalitis has been extensively studied, HSV-1 generalized infections and subsequent acute liver failure are less well understood. We previously demonstrated that IFN-αβγR(−/−) mice are exquisitely susceptible to liver infection following corneal infection with HSV-1. In this study, we used bone marrow chimeras of IFN-αβγR(−/−) (AG129) and wild-type (WT; 129SvEv) mice to probe the underlying IFN-dependent mechanisms that control HSV-1 pathogenesis. After infection, WT mice with either IFN-αβγR(−/−) or WT marrow exhibited comparable survival, while IFN-αβγR(−/−) mice with WT marrow had a significant survival advantage over their counterparts with IFN-αβγR(−/−) marrow. Furthermore, using bioluminescent imaging to maximize data acquisition, we showed that the transfer of IFN-competent hematopoietic cells controlled HSV-1 replication and damage in the livers of IFN-αβγR(−/−) mice. Consistent with this, the inability of IFN-αβγR(−/−) immune cells to control liver infection in IFN-αβγR(−/−) mice manifested as profoundly elevated aspartate transaminase (AST) and alanine transaminase (ALT) levels, indicative of severe liver damage. In contrast, IFN-αβγR(−/−) mice receiving WT marrow exhibited only modest elevations of AST and ALT levels. These studies indicate that IFN responsiveness of the immune system is a major determinant of viral tropism and damage during visceral HSV infections. IMPORTANCE Herpes simplex virus 1 (HSV-1) infection is an incurable viral infection with the most significant morbidity and mortality occurring in neonates and patients with compromised immune systems. Severe pathologies from HSV include the blindness-inducing herpetic stromal keratitis, highly debilitating and lethal herpes simplex encephalitis, and generalized infections that can lead to herpes simplex virus-induced acute liver failure. While immune compromise is a known factor, the precise mechanisms that lead to generalized HSV infections are unknown. In this study, we used and developed a mouse model system in combination with real-time bioluminescence imaging to demonstrate the relative importance of the immune and nonimmune compartments for containing viral spread and promoting host survival after corneal infection. Our results shed light on the pathogenesis of HSV infections that lead to generalized infection and acute liver failure.